PENGEMBANGAN VIDEO PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN MINAT BELAJAR SISWA - Zai, Yernita Putri; Lase, Asali; Lahagu, Arianto; Harefa, Yearning (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2024)
The lecture method is very disliked by today's students. The tendency of teachers to use this method often makes students sleepy in class, as a result, learning objectives will not be achieved and have an impact on students' interest in learning. The purpose of this study was to determine the development of interactive learning videos in increasing students' interest in learning. The research method used is the research and development method (Research and Development). The results of the study showed that the content of the material and handling of problems by material experts were very valid with a percentage of 91% (very valid), while the results of the feasibility of interactive learning media reached 95% (very valid). The response of students to the interactive learning video individual test was 93% (very practical) while in the field test it reached 92% (very practical) while the results of student learning interest based on the questionnaire that had been distributed reached a percentage of 93%. The effectiveness of interactive learning videos on economic activity material with learning completeness of 66% with a very high effectiveness category. It can be concluded that interactive learning videos have proven to be effective in increasing students' interest in learning.